Case report: Intra-abdominal aggressive fibromatosis: A rare cause of hyperemesis - Zou, Zilin; Ye, Guannan; Xu, Saiqun; Liu, Wei; Wang, Weining (Frontiers in Surgery, 2023)
Rationale: Aggressive fibromatosis is a rare and locally infiltrative monoclonal fibroblastic proliferation with lack of metastatic potential. We describe a rare case of intra-abdominal aggressive fibromatosis on young female with hyperemesis. Patient concerns: A 23-year-old female was admitted with hyperemesis and loss of weight. Diagnoses: According to imaging findings and immunohistology findings, a diagnosis of intra-abdominal aggressive fibromatosis was formulated. Outcomes: After the surgery, no evidence of local recurrence was noted during the 6 months of follow-up. Lessons: AF may explain why pregnant women may have severe hyperemesis .